If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(m + -3) = 0 Reorder the terms: 3(-3 + m) = 0 (-3 * 3 + m * 3) = 0 (-9 + 3m) = 0 Solving -9 + 3m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 3m = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 3m = 0 + 9 3m = 0 + 9 Combine like terms: 0 + 9 = 9 3m = 9 Divide each side by '3'. m = 3 Simplifying m = 3
| 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z | | 2(4a+5)=1.8a-3 | | 2(5-4x)=-46 | | 29-9x=-5(7x+2)-5(-4-5x) | | 2x+11=2x-19 | | -8m-24=24 | | 5-2(y-5)=267 | | y+6n=6n+5 | | 40x=60y | | 4z+11=2z+7 | | 5y+6=-y+24 | | 42-14x=-5(6x+2)-5(-8-3x) | | 2(3a+1)=12+2(4a+3) | | 8-5x-4=-6x+6 | | 3m-4=20 | | 25*x^2-16*x^2= | | Y+14=10 | | x^0+1=0 | | 14x-12+30=4 | | 8z-9=90 | | 2z+y=4z+11 | | z=6z+18 | | 8z-9=1z+9 | | (4x-2)=(4x+10) | | 3x+2m+x+3m+2= | | 7.5(a+1.6)=29.25 | | 2x+3y-5=16 |